Sexual Violence in the Creative Industries: A Minority Local Cultural Perspective - Husnurrosyidah, Husnurrosyidah; Irawan, Arya Andi; Kuncoro, Amin; Amaroh, Siti (Journal of Economics and Public Health, 2025)
This study aims to explain the social meaning of Tongtek artistic practices and identify factors contributing to the normalization of sexual violence against female artists. The research design uses qualitative research with snowball sampling techniques. Informants in this study consist of: 1) art connoisseurs (users); 2) cultural organizers; 3) female artists in Tongtek art. The results of the study indicate that Tongtek artistic practices are local traditions and cultures that have adapted to contemporary cultural conditions. Although they have historical and aesthetic value, these practices also harbor complex problems, especially related to gender and power relations. Factors contributing to the normalization of sexual violence against female artists in this context include: 1) the still-strong patriarchal cultural construction; 2) the unequal power relations between female artists and art connoisseurs; 3) the lack of regulation and legal protection for female artists; and 4) the internalization of cultural norms that consider sexual violence as normal in certain contexts. However, in reality, this phenomenon has not been able to be analyzed and explained so that it becomes one of the local cultures that contributes to the development of culture in modern society. It is hoped that the research findings will provide critical reflection for stakeholders on preserving local culture without compromising the rights and dignity of female artists. Thus, Tongtek art is viewed not only as a cultural heritage but also as a medium for promoting social justice and gender equality in society.